High-performance Lithium-ion anodes with hierarchically assembled single-crystal SnO2 nanoflake spheres - Liu, Zhaoyang (2013)
A large-scale hierarchical assembly route is reported for the formation of SnO2 on the nanoscale that contains rigid and robust spheres with irregular channels for rapid access of Li ions into the hierarchically structured interiors. Large volume changes during the process of Li insertion and extraction are accommodated by the SnO2 nanoflake spheres’ internal porosity. The hierarchical SnO2 nanoflake spheres exhibit good lithium storage properties with high capacity and long-lasting performance when used as lithium-ion anodes. A reversible capacity of 517 mA h g−1, still greater than the theoretical capacity of graphite (372 mA h g−1), after 50 charge–discharge cycles is attained. Meanwhile, the synthesis process is simple, inexpensive, safe, and broadly applicable, providing new avenues for the rational engineering of electrode materials with enhanced conductivity and power.